Estado, conflictos y pronóstico del complejo de humedales costeros de Punta Mogotes, Mar del Plata, Buenos Aires, Argentina - De Marco, S. G. (2006)
A wetland and lagoon complex is located southwards Mar del Plata city (38º 02´40´´ S and 57º 32´00´´ O, Buenos Aires, Argentina). The study area limits Northwards with oil storages for harbor purposes and with fish processing plants, Northwestwards with a palaeocliff developed during Holocene marine entry, on palaeo and cainozoic grounds. Southeastwards, with the Punta Cantera outpoint. Its northern borderline corresponds to the Natural Reserve from the Mar del Plata harbor. These are freshwater lagoons although their proximity to the sea. The main environmental problem within these wetlands and lagoons are due to human pressure (tourism, municipal, domestic and industrial sewage dumping, storage of illegal solid residues). This is accompanied by the lack of environmental planning. Moreover, information from this complex ecosystem is scarce, punctual and unpublished in the scientific literature. The present work includes the compilation and review of available flori-faunistic and environmental information -unpublished within the scientific literature-, the analysis of these wetlands´ historic evolution, and evaluates the physicochemical condition of their waters. Within this framework, a plannification and management project is proposed, which includes the study and monitoring of these wetlands, which also promotes both educational and transference activities, in order to reinforce their natural resources valorisation.